Analisis Nilai Agama Islam dalam Novel Sebuah Surau Karya Artie Ahmad - Abdilla Zikhri, Rijali; Shomary, Sudirman (Sajak: Jurnal Penelitian dan Pengabdian Sastra, Bahasa, dan Pendidikan, 2023)
Religious values are values that discuss the concept of belief or trust in the form of a relationship that governs humans and their God. The author is interested in analyzing Islamic religious values in the novel A Surau by Artie Ahmad because the author views Islamic religious values as very important to be discussed in every area of Muslim life and used as a guide for life in a better direction. Problems in the research: 1) What is the value of the Islamic religion in the aspect of faith in Artie Ahmad's novel A Surau? 2) What is the value of the Islamic religion in the aspect of worship in the novel A Surau by Artie Ahmad? 3) What is the value of the Islamic religion in the moral aspect in the novel A Surau by Artie Ahmad?. The approach that the author uses is a qualitative approach, this type of research is a library, the method used is descriptive, and the analysis uses hermeneutic techniques. The results of the study concluded: (1) The value of the Islamic religion aspect of aqidah 52 data. (2) The value of Islamic religious aspects of worship 37 data. (3) Islamic religious values in moral aspects 52 data.